2019
DOI: 10.1124/dmd.118.085167
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of the Site(s) of Metabolism and Binding Modes of Protein Kinase Inhibitors Metabolized by CYP3A4

Abstract: Protein kinase inhibitors (KIs), which are mainly biotransformed by CYP3A4-catalyzed oxidation, represent a rapidly expanding class of drugs used primarily for the treatment of cancer. Ligand-and structure-based methods were applied here to investigate whether computational approaches may be used to predict the site(s) of metabolism (SOM) of KIs and to identify amino acids within the CYP3A4 active site involved in KI binding. A data set of the experimentally determined SOMs of 31 KIs known to undergo biotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…It is intriguing that none of the prior computational studies identified Thr224 as residue that could facilitate the ligand association to CYP3A4 [ 17 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ]. The CYP3A4–fluorol complex is the fourth structure where the ligand binding mode is stabilized via direct H-bonding to Thr224 [ 5 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that none of the prior computational studies identified Thr224 as residue that could facilitate the ligand association to CYP3A4 [ 17 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ]. The CYP3A4–fluorol complex is the fourth structure where the ligand binding mode is stabilized via direct H-bonding to Thr224 [ 5 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking experiment was conducted using a slightly modified protein crystal structure of CYP3A4 complexed with ketoconazole (PDB ID: 2V0M) [8][9]. The ligands used in this investigation were four major compounds from C. asiatica and three known compounds from O. stamineus as reported in previous literature [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking experiments were conducted using the Surflex-Dock docking suite (31) as previously reported (11,32). The resulting binding poses were ranked according to the total score (SYBYL Surflex-Dock).…”
Section: Computational Studies Of the Docking Of Sor And Sno Into The Active Sites Of Cyp2c8 And Cyp2c9mentioning
confidence: 99%